The Prevalence and Infection’s Degree of Gastrointestinal Worm of Local Chicken (Gallus domesticus) in Kramat Village, District of Bangkalan, Madura, East Java Indonesia - Ellza Agatha Damayanti; Poedji Hastutiek; Agnes Theresia Soelih Estoepangestie; Nunuk Dyah Retno Lastuti; Kusnoto Kusnoto; Endang Suprihati (Universitas Airlangga, 2019)
The study was aimed to know the prevalence and level of gastrointestinal worm investation of local chicken (Gallus domesticus) in Kramat Village, district of Bangkalan, Madura East Java province. The samples used in the study were 100 faeces of kampung chicken. using sedimentation and floating method. Faeces samples were tested, than followed by microscopically test to identify the worm is species. The result showed that in 38 out of 100 samples could be indentified some worm species as followed : Capillaria sp.14 (36,8%), Railletina 7 (18,4%), Hymenolepis 16 (42,1%) and Heterakis gallinarum 1 (2,6%). Using Mann Whitney U-test could be differentiated the level of the infection with an average of 45.53 in cock, while in hen with an average of 55.47. There was no significancy (p>0,05) on the level of worm gastrointestinal infection of different sex of kampung chicken.